Training on Tour Package Development and Tourism Interpretation for the Development of Eduwisata Desa Emas Sodong - Kristiana, Yustisia (Panrannuangku Jurnal Pengabdian Masyarakat, 2025)
Eduwisata Desa Emas Sodong, located in Tigaraksa District, Tangerang Regency, possesses significant potential for educational tourism but has not yet been optimally developed by the local community. The limited capacity of residents in designing tour packages and conducting tourism interpretation has become a key obstacle to the village’s tourism development. This Community Service (PkM) program was implemented to strengthen the community’s capacity through training on tour package development and tourism interpretation based on local potential. The activity involved village tourism managers and community groups as active participants. The results showed an increase in participants’ knowledge and skills in designing educational tourism activities, as well as improved confidence in interpreting local potentials to visitors. Overall, this program contributed to strengthening the management of Eduwisata Desa Emas Sodong and encouraged the sustainable, community-based development of the educational tourist attraction.